Development of conditioned medium derived from rat amniotic fluid stem cells suitable for restoration of diabetic wound - Abdul Ghofar, Hasfar Amynurliyana (2017)
Wound in diabetics is a slow healing and chronic process. Stem cells have been reported to mobilize the wound site, by secreting cellular growth factors and cytokines during their cultivation by promoting angiogenesis and remodeling of extracellular matrix (ECM), creating a favorable local environment for wound healing. The conditioned medium (CM) is a medium containing growth factors and cytokines cultivated in viable optimum environment for a certain period of time. These factors may promote the growth of new cells especially in wound microenvironment. Therefore, this work is conducted to establish and characterize rat amniotic fluid stem cells conditioned medium (rAFSC-CM) that is suitable for in vitro diabetic wound healing model using diabetic human dermal fibroblasts (HDF-D). To achieve this aim, a suitable number of rAFSCs density, which has been isolated, identified, and confirmed were used in the preparation of CM. The cells density at 0.25×106 cells/mL was used to prepare the CM with the presence of leukemia inhibitory factor (LIF+) and absence of LIF (LIF-). Cell proliferation assays and scratch test assays were conducted to substantiate the ability of rAFSCs-CM in enhancing the Diabetic Human Dermal Fibroblast (HDF-D) cell proliferation and migrations. The expression of molecular markers such as TGF-β1, VEGF, IL-6, IL-1β, and TNF-α in CM were identified using Enzyme Linked Immunosorbent Assay (ELISA) and Western’s blotting technique. The results revealed rAFSC-CM has significantly improved the migration, viability, and proliferation of HDF-D cells. ELISA and Western Blot indicated that the rAFSCs-CM contains various growth factors that are known to be important in wound healing including TGF-β1, VEGF, IL-6, IL-1β, and TNF-α. From the data observed, it was suggested that low concentration (25%) of rAFSC-CM with the absence of LIF (LIF-) showed the most potential CM with a good potential of proliferation and migration activity. As a conclusion, this study showed that rAFSCs secreted high levels of cytokines and growth factors that enhance the wound healing, and further studies using specific mechanism experiments in vivo are needed to uncover and improve its effectiveness in cell-free therapies to encourage the healing of diabetic skin wound.